Espécies exóticas na comunidade vegetal do Parque Estadual Sumaúma : potencial de impacto, uso humano e propostas de controle - Magalhães, Lana Cynthia Silva (2015)
The introduction of exotic species is the first cause of loss of biodiversity in protected areas. However, although recognized the threat of these species, the scientific basis for the definition and quantification of impacts is still shy, and lack of a common framework for measuring them. Despite the negative effects that may result can not be denied that the alien species are beneficial, especially economic, and have a close relationship with human activities. However, their presence is not compatible with protected area objectives, where their populations must be controlled. Thus, the aim of this study was to characterize the potential impact of exotic plants for the plant community of Sumaúma State Park. The specific objectives include characterizing the floristic community; evaluate the potential impact of alien species; investigate human use assigned to these species and to propose actions for the proper management of exotic species. For this, settled 30 plots of 20x20 me subplots of 1x1 m, 15 installed 2 m from the boundaries of the Park and the other 120 meters, being located in the inner region. It included all individuals belonging to the tree and shrub stratum with DBH ≥ 2.5 cm and the sub-plots were registered those who were between 5 cm to 1 m, including arboreal seedlings. The estimated phytosociological parameters for the community were density, frequency, dominance and importance value index. The exotic impact was assessed by abundance, phytosociology and Environmental Exotic Impact Index. The characterization as for human use and management was carried out through consultations to specific databases and literature. We identified 1,947 individuals, 61 families and 169 genera. As for exotic were 11 species and 89 individuals. The species with the highest density in the tree and shrub stratum was aduncum and herbaceous Pariana sp, both native. Among the exotic species were 11 and 89 individuals, most concentrated near the edge of the fragment area. Four of the seven installments in the presence of exotic tree and shrub stratum showed IIAE below or close to 0.8 - that is any indication of impact. The herb layer, the impact can be proven by the greater abundance of species Alocasia macrorrhizos and Megathyrsus maximus, compared to native species. Among the 11 registered alien species, 10 have potential invasion and some human use, which highlights the number of fruit species. The association between the mechanical and chemical control techniques proved the most effective for the control of most species. The survey on the occurrence of exotic and control proposals are the first steps that management actions can be taken and contribute to the conservation of unique biodiversity of the park. KEY-WORDS: Biological Invasion; Impact Index; Phytosociology; Abundance.